Antimicrobial activity of leaf extracts of Euphorbia paralias L. and Melilotus sulcatus Desf. against some pathogenic microorganisms - Miloud, Miloud M.; Senussi, Najma A. (Current Botany, 2021)
The present study was aimed to investigate the antimicrobial potential of leaf extracts of Euphorbia paralias and Melilotus sulcatus against four bacterial species Staphylococcus aureus, Pseudomonas aeruginosa, Escherichia coli and Klebsiella sp. and two fungal species Asperigillus niger and Aspergillus flavus. The agar well diffusion assay was used to evaluate the antimicrobial activity. The effect of these extracts was most effective against the bacterial species compared to the fungal species at a used concentration (100 mg/ml). Methanolic extracts of selected plants displayed good antimicrobial activity against all tested microorganisms species, while, no activity for aqueous extracts against tested fungal species. Methanolic extracts were the most effective plant extracts against all tested bacterial species, with MIC and MBC reached 6.2 and 12.5 mg/ml, except Klebsiella sp. which was less sensitive to M. sulcatus methanolic extract and its MIC and MBC reached 12.5 and 25 mg/ml, respectively. These plant extracts which proved to be potentially effective can be used as bioactive agents to control microorganisms caused for diseases and they can be used naturally in the human and veterinary healthcare systems.